The Gold Coast. 1653 - 1655. - Government of Gold Coast (Government of Gold Coast, 1653)
The Dutch Director-General on the Gold Coast. Jacob Ruichaver. 1653 - 1655. (Vide Under 1648-1652. N.
Furley Collection
Keywords: Gold Coast